Why Kenyan rangeland cattle need new methane emission factors - Gurmu, Endale Balcha; Arndt, Claudia (International Livestock Research Institute, 2025)
This blog explains why default methane emission factors used in national greenhouse gas inventories do not adequately represent Kenya’s diverse rangeland and pastoral cattle systems. Using site-specific measurements from three ranching and pastoral systems in southern Kenya, the study demonstrates how differences in breed, body weight, feed quality, and animal mobility lead to substantial variation in methane emissions. The findings highlight the importance of adopting IPCC Tier 2, system-specific emission factors to improve inventory accuracy and support effective climate mitigation strategies for Kenyan livestock systems.